Pengembangan Paket Wisata Berdasarkan Segmentasi Psikografis Wisatawan Pendaki Gunung Indonesia di Kawasan Konservasi Annapurna, Nepal - Kurnia Fahmy Ilmawan (JURNAL NASIONAL PARIWISATA, 2023)
Annapurna Conservation Area is a destination for Indonesian outbound tourist, specifically in pendakian gunung as special interest tourism segments. This paper’s identified Indonesian Trekkers psychographic segmentation through their travel career pattern and develop a pendakian gunung package for Indonesian tourists based on their travel career pattern in Annapurna Conservation Area. Psychographic segmentation based on Indonesian tourist travel motives, level of travel experiences, level of pendakian gunung experiences, level of preparation and participation, and life stage level. Thus, Indonesia trekkers in Annapurna categorized as younger and experienced, mid-life and moderately experienced, mid-life and experience, and high travel career refers to their travel career pattern. Pendakian gunung packages are developed based on travel career pattern with strategies to introduces a contrast of landscape, advance pendakian gunung activities, self-actualized and wellness endurance, and as technical and management advance for Indonesia trekkers in Annapurna Conservation Area.